Payment for Ecosystem Services from Forests - Jennifer Alix-Garcia; Hendrik Wolff (Institute for the Study of Labor (IZA), 2014)
Every year between 2000 and 2010, our planet lost native forests roughly the size of Costa Rica. (FAO, 2010). This rapid deforestation has dramatically changed the chemical composition of the world's atmosphere, the level of biodiversity, and the presence of vegetation key to maintaining watershed function and preventing landslides. There has been a boom in the design of local and international policy instruments to prevent further deforestation and encourage forest growth. This paper reviews the theory and evidence surrounding forest-related Payment for Ecosystem Services (PES) schemes intended to slow and reverse deforestation. We cover the most recent work touching on a range of issues related to PES programs, including research on targeting, contract design, environmental effectiveness, challenges to program implementation, spillovers, and distributional considerations of conditional cash transfers. We also highlight areas of potential future research.
Keywords: H23; H43; J43; Q23; 330; environmental policy; deforestation; afforestation; reforestation; climate change; conditional cash transfers; PES